2023
DOI: 10.2340/actadv.v103.5578
|View full text |Cite
|
Sign up to set email alerts
|

Upadacitinib for Successful Treatment of Alopecia Universalis in a Child: A Case Report and Literature Review

Abstract: is missing (Short communication)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…To our knowledge, there has been no prior report of successful treatment of comorbid AD and AA by switching to abrocitinib after dupilumab failure (Table 2). 18,[31][32][33][34][35] Throughout our 1-year follow-up, we observed a favorable response to abrocitinib with no adverse reactions, suggesting its safety in treating such conditions in children.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…To our knowledge, there has been no prior report of successful treatment of comorbid AD and AA by switching to abrocitinib after dupilumab failure (Table 2). 18,[31][32][33][34][35] Throughout our 1-year follow-up, we observed a favorable response to abrocitinib with no adverse reactions, suggesting its safety in treating such conditions in children.…”
Section: Discussionsupporting
confidence: 51%
“…18 Based on this review, we have summarized the latest reports of JAK inhibitor treatment for pediatric AA in the past 2 years (Table 1). 18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Six cases involved the use of upadacitinib (selective JAK1 inhibitor) and abrocitinib (selective JAK1 inhibitor) in treating pediatric patients with AA, showing good tolerability. 18,[31][32][33][34][35] Upadacitinib and abrocitinib have been approved for severe AD in children aged ≥12 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Yu and Ren reported a case of successful treatment with UPA in a child with alopecia universalis (AU) and mild AD (EASI 2.5). 112 The patient experienced substantial hair regrowth after 4 weeks of UPA treatment, with a marked improvement in the SALT score from 100% at baseline to 0% at week 12. Similarly, Bourkas and Sibbald reported a pediatric patient with AA and severe AD achieving a reduction in the SALT score from 95.1±9.6 at baseline to 77.6±28.2 at week 4, 113 indicating a positive response to UPA therapy.…”
Section: Patients With Concomitant Autoimmune or Inflammatory Skin Di...mentioning
confidence: 86%
“…More data regarding the pediatric populations are coming from case series. The study by Dianhe Yu and Yunqing Ren reported a case of successful treatment with UPA in a child with alopecia universalis (AU) and mild AD (EASI 2.5) (112). The patient experienced substantial hair regrowth after 4 weeks of UPA treatment, with a marked improvement in the SALT score from 100% at baseline to 0% at week 12.…”
Section: Alopecia Areatamentioning
confidence: 99%